Tracing the Sociological Roots of Terrorism in Indonesia: The Role of Family Dysfunction in the Perspective of Islamic Family Law - Herniwati, Herniwati; Kurniati, Kurniati; Mustafa, Zulhas'ari (Journal of Nafaqah, 2025)
The phenomenon of family involvement in acts of terrorism in Indonesia indicates a shift in the pattern of radicalization from the public sphere to the private sphere. This research aims to trace the sociological roots of terrorism by emphasizing the role of family dysfunction and reviewing the relevance of Islamic family law principles in preventing the radicalization process early on. The method used is qualitative with a case study approach, through document analysis, literature study, and in-depth interviews with relevant resource persons, such as former terrorists, sociology experts, and Islamic law experts. The results show that most terrorists come from dysfunctional families, characterized by a lack of communication, neglectful or harsh parenting, and the absence of moderate spiritual role models. The radicalization process takes place within the home, through closed recitations, digital extreme content, and internal indoctrination. These findings indicate the non-implementation of maqashid sharia principles in family life, such as the protection of the soul, mind and offspring. Therefore, the de-radicalization approach must be multidisciplinary by integrating the perspectives of sociology, Islamic law and family education. Islamic family law not only functions as a legal-formal norm, but also as an ethical and practical guideline in building family resilience as the first bulwark against violent ideologies.